Mutational Screening of LCA Genes Emphasizing RPE65 in South Indian Cohort of Patients - Verma, Anshuman (Public Library of Science, 2013)
BACKGROUND: Leber congenital amaurosis (LCA) is the most severe form of inherited retinal visual impairment in children. So far, mutations in more than 20 genes have been known to cause LCA and among them, RPE65 is a suitable candidate for gene therapy. The mutational screenings of RPE65 and other LCA genes are requisite in support of emerging gene specific therapy for LCA. Therefore, we have carried out a comprehensive LCA genes screening using a combined approach of direct sequencing and DNA microarray based Asper chip analysis. METHODOLOGY/PRINCIPAL FINDINGS: Thirty clinically diagnosed index LCA cases from Southern India were screened for coding and flanking intronic regions of RPE65 through direct sequencing. Among thirty, 25 cases excluded from RPE65 mutations were subjected to Asper chip analysis, testing 784 known pathogenic variations in 15 major LCA genes. In RPE65 screening, four different pathogenic variations including two novel (c.361insT & c.939T>A) and two known (c.394G>A & c.361delT) mutations were identified in five index cases. In the chip analysis, seven known pathogenic mutations were identified in six index cases, involving genes GUCY2D, RPGRIP1, AIPL1, CRX and IQCB1. Overall, 11 out of 30 LCA cases (36.6%) revealed pathogenic variations with the involvement of RPE65 (16.6%), GUCY2D (10%), RPGRIP1 (3.3%), AIPL1 (3.3%) and CRX & IQCB1 (3.3%). CONCLUSIONS/SIGNIFICANCE: Our study suggests that such combined screening approach is productive and cost-effective for mutation detection and can be applied in Indian LCA cohort for molecular diagnosis and genetic counselling.